Cerámica de lujo medieval en dos castillos de la mitra compostelana = Medieval luxury ceramics in two castles of the ‘Compostela’s Miter’ - Prieto Martínez, María del Pilar; Alonso Toucido, Francisco; Lantes Suárez, Óscar; Casal García, Raquel; Acuña Castroviejo, Fernando (Estudios Humanísticos. Historia, 2020)
Los castillos de Rocha Branca y Rocha Forte son todo un referente dentro del arzobispado medieval de Santiago, en ellos residirían varios arzobispos, convirtiéndose principalmente Rocha Branca en un auténtico recinto palacial. Debido a ese contexto, los materiales recuperados en los mismos son piezas vidriadas de lujo importadas. Se busca contribuir al estudio de estas piezas, así como a la posible definición de sus lugares de fabricación y técnicas, mediante la aplicación de la arqueometría. Gracias a los análisis sobre cinco piezas hemos podido retrotraernos a las producciones cerámicas de época bajomedieval y moderna documentadas en ambos recintos fortificados The castles of Rocha Branca and Rocha Forte are an important reference point with regard to the mediaeval archbishopric of Santiago, which were home to several archbishops, with the castle of Rocha Branca in particular becoming a truly palatial compound. Because of this context, the materials that have been found are luxurious, imported glazed pieces. The aim os this paper is to contribute towards the study of these pieces, as well as helping to possibly define where they were made and the techniques used, through the application of archaeometry. Thanks to an analysis of five pieces, we have been able to categorise ceramic products from the late mediaeval and modern period found in both fortified compounds.